Estratégias utilizadas nas empresas para garantir as finanças e se consolidar no mercado altamente competitivo em tempos de pandemia - SALES, Renata Ueno; SANTOS, Bruna Luiz dos; SANTOS, Elba Camila Bernardes (My University, 2023)
Este artigo visa apresentar um estudo para contribuir com o meio empresarial, demonstrando as diretrizes utilizadas pelos gestores durante a pandemia. Buscou-se aprofundar o conhecimento sobre os recursos escolhidos relacionados às estratégias e finanças para que as empresas conseguissem minimizar a crise econômica decorrente da pandemia. Devido ao isolamento social e ao lockdown as empresas precisaram adaptar-se às novas normas de restrições sugeridas pela Organização Mundial de Saúde, principalmente aquelas que não faziam parte do grupo de serviços considerados essenciais e que precisaram baixar suas portas e foram obrigadas a recorrer a inúmeras táticas empresariais, utilizando a criatividade para se manterem ativas no mercado atual. Assim, esta pesquisa buscou relatar como a empresa se organizou para continuar garantindo as receitas e a importância do trabalho dos gestores para manter a equipe engajada, motivada e principalmente atingindo as metas estabelecidas, de modo agarantir que a empresa não entrasse em falência. Trata-se de uma pesquisa de campo, explicativa e empírica que buscou demonstrar como os empresários, empreendedores e gestores procederam para que a crise não os afetasse de maneira irreversível. São expostas as estratégias utilizadas pelos mesmos, sejam elas de inovação ou até mesmo uma mudança de seguimento visando garantir a vida ativa da organização, procurando estabelecer novos métodos e com isso, fazer com que a empresa garanta a sua entrada e saída de caixa, mantendo a produção e os insumos e vendas ativas, para assim poderem se consolidar no mercado altamente competitivo em tempo de pandemia.Palavras-chave: estratégia; gestão financeira; pandemia.Strategies used in companies to ensure finances and consolidate in the highly competitive market in times of pandemicAbstractThis research aims to present a study to contribute to the business environment, demonstrating the guidelines used by managers during the pandemic. We sought to deepen the knowledge about the chosen resources related to strategies and finances so that companies could minimize the economic crisis resulting from the pandemic. Due to social isolation and lockdown, companies had to adapt to the new rules of restrictions suggested by the World Health Organization, especially those that were not part of the group of services considered essential and that had to lower their doors and were forced to resort to numerous business tactics, using creativity to stay active in current market. Thus, this research sought to report how the company was organized to continue guaranteeing revenues and the importance of the managers' work to keep the team engaged, motivated and mainly reaching the established goals, in order to ensure that the company did not go bankrupt. It is a field, explanatory and empirical research that sought to demonstrate how businessmen, , entrepreneurs and managers proceeded so that the crisis did not affect them irreversibly. The strategies used by them are exposed, be they innovation or even a change of follow- up aiming to guarantee the active life of the organization, seeking to establish new methods and with that to make the company assure its cash inflow and outflow, maintaining the production and active inputs and sales, in such a way that they can consolidate themselves in the highly competitive market in times of pandemic.Keywords:strategy; financial management; pandemic.

This research aims to present a study to contribute to the business environment, demonstrating the guidelines used by managers during the pandemic. We sought to deepen the knowledge about the chosen resources related to strategies and finances so that companies could minimize the economic crisis resulting from the pandemic. Due to social isolation and lockdown, companies had to adapt to the new rules of restrictions suggested by the World Health Organization, especially those that were not part of the group of services considered essential and that had to lower their doors and were forced to resort to numerous business tactics, using creativity to stay active in current market. Thus, this research sought to report how the company was organized to continue guaranteeing revenues and the importance of the managers' work to keep the team engaged, motivated and mainly reaching the established goals, in order to ensure that the company did not go bankrupt. It is a field, explanatory and empirical research that sought to demonstrate how businessmen, , entrepreneurs and managers proceeded so that the crisis did not affect them irreversibly. The strategies used by them are exposed, be they innovation or even a change of follow- up aiming to guarantee the active life of the organization, seeking to establish new methods and with that to make the company assure its cash inflow and outflow, maintaining the production and active inputs and sales, in such a way that they can consolidate themselves in the highly competitive market in times of pandemic
Strategies used by companies to secure finances and consolidate themselves in the highly competitive market in times of a pandemic
Keywords: Pandemias; Crise financeira; Gestão e Negócios